Investigating The Indonesian Senior High School’s English Classroom Anxiety and Its Factors - Mahendra, Isnan; Wija Putra, Bambang Arya; Andika Hudori, Rizki Febri (English Education Study Program, 2023)
The process of learning English as a foreign language is not easy as students face various difficulties and one of them is anxiety. Ketsman, (2012) and Yilmaz, (2011) stated that student's performance and achievement are affected by the teacher's effectiveness, and one of the teacher's roles is to reduce anxiety in the classroom by creating a friendly and supportive atmosphere in the classroom. For this purpose, it is important to know the level of anxiety of foreign language learners. The present study aimed to investigate the students' perceived level of foreign language anxiety among Indonesian high school students based on the Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz et al. The present study was a survey design. This design focuses on describing trends in a large group of individuals (Creswell, 2012). The results of the present study showed that anxious students were quite common in foreign language classrooms within the scope of this study. The participants in the present study had a moderate-level of anxiety, and the three factors included in the research instrument contributed to it to varying degrees.